2019
DOI: 10.2478/cipms-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Chromone-3-aldehyde derivatives – sirtuin 2 inhibitors for correction of muscular dysfunction

Abstract: The aim of the study was to evaluate experimentally, the myoprotective effect of new chromone-3-aldehyde derivatives in conditions of muscular dysfunction and to establish a potential mechanism of myoprotective activity – the blockade of the function of sirutin 2. Materials and methods. The effect of new chromone-3-aldehyde derivatives on the development of muscular dysfunction under the conditions of an electromiostimulation test, was studied. The degree of muscle fatigue was evaluated in the «grip-strength» … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
0
0
1
Order By: Relevance
“…клиническая фармакология пероксид-радикала как в IFM, так и в SSM субпопуляциях, что может быть связано с разобщающим действием данных препаратов на митохондриальный метаболизм. Регуляторный потенциал производных 3-формилхромона в отношении митохондриального биогенеза может быть опосредован влиянием на белки семейства сиртуинов [17], отвечающих практически за все аспекты функциональной активности митохондрий, включая процессы аутофагии, окислительного метаболизма и синтеза органелл de novo [18].…”
Section: оригинальные исследованияunclassified
“…клиническая фармакология пероксид-радикала как в IFM, так и в SSM субпопуляциях, что может быть связано с разобщающим действием данных препаратов на митохондриальный метаболизм. Регуляторный потенциал производных 3-формилхромона в отношении митохондриального биогенеза может быть опосредован влиянием на белки семейства сиртуинов [17], отвечающих практически за все аспекты функциональной активности митохондрий, включая процессы аутофагии, окислительного метаболизма и синтеза органелл de novo [18].…”
Section: оригинальные исследованияunclassified
“…For example, the compound 4'-methoxy-2-styrylchromone showed cell proliferation activity of 70 % in HeLa cells (human cervical tumour), and 25 % in CHO (Chinese hamster ovary cells). 4 Chromone derivatives bearing different dithiocarbamate (234-237) 5 or styryl (238) 6,7 groups have emerged as promising candidates due to their high efficacy and broad spectrum against HCCLM-7, HeLa, MDA-MB-435S, SW-480, Hep-2, MCF-7 (breast adenocarcinoma), and NCl-H460 (non-small cell lung cancer). Further analysis of flow-activated cell sorting revealed that these compounds arrested the cell cycle of SW-480 and MDA-MB -435S in a dose-dependent manner at G2/M phase, and could have an apoptosis-inducing effect on these tumour cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4] Various in vitro, in vivo, and clinical studies have demonstrated the role of chromones in alleviating allergies, reducing oxidative damage, inhibiting cancer, infections and inflammation, and treating neurological and psychiatric disorders. [5][6][7] Of all the ligands used in this study, maltol is the best known. Nowadays, compounds of maltol and some transition metals such as vanadium are known to have excellent insulinomimetic properties, while their antitumour properties are almost unknown.…”
Section: Introductionmentioning
confidence: 99%